Mechanical performance of FRP-confined geopolymer concrete under seawater attack. Issue 6 (April 2020) - Alzeebaree, Radhwan; Çevik, Abdulkadir; Mohammedameen, Alaa; Niş, Anıl; Gülşan, Mehmet Eren
In the study, mechanical properties and durability performance of confined/unconfined geopolymer concrete and ordinary concrete specimens were investigated under ambient and seawater environments. Some of the specimens were confined by carbon fiber and basalt fiber–reinforced polymer fabric materials with one layer and three layers under chloride and ambient environments to observe mechanical strength contribution and durability performances of these hybrid types of materials. These fiber-reinforced polymer fabric materials were also evaluated in terms of retrofit purposes especially in the marine structures. In addition, microstructural evaluation is also conducted using scanning electron microscope on geopolymer concrete and ordinary concrete specimens to observe the amount of deterioration in microscale due to the chloride attacks. Results indicated that confined specimens exhibited enhanced strength, ductility, and durability properties than unconfined specimens, and the degree of the enhancement depended on the fiber-reinforced polymer confinement type and the number of fiber-reinforced polymer layer. Specimens confined by carbon fabrics with three layers showed superior mechanical properties and durability performance against chloride attack, while specimens confined by basalt fabrics with one layer exhibited low performance, and unconfined specimens showed the worst performance. Both fiber-reinforced polymer fabric materials can be utilized as retrofit materials in structural elements against chloride attacks. The results also pointed out that seawater attack reduced the ductility performance of the geopolymer concrete and ordinary concrete specimens. Furthermore, geopolymer concrete specimens were found more durable than the ordinary concrete specimens, and both types of concretes exhibited similar fracture properties, indicating that geopolymer concrete can be utilized for structural elements instead of ordinary concretes.